Cidadania e solidariedade: uma análise do discurso de membros da Primeira Igreja Presbiteriana de Vitória a partir de seu trabalho social - Nalesso, Darison (2010)
Reflecting the church and its social work should be done in an expanded context, because many actions are undertaken by various institutions in our society. The extension of these social practices by the church is due to lack much of the state taking responsibility for the social demands of the population. Becomes important, therefore, to assess whether these institutions have been offering this work so as to form citizens capable of understanding their role as citizens, and why not say, of solidarity. This study aims to discuss and analyze these social practices based on the foundational of the following categories: citizenship and solidarity. It is understood that these categories are of prime importance for the society we live in, especially in regard to the coping of the various expressions of social issues. The theme of citizenship has been built along the historical, favoring the development of so-called civil rights, political rights, social and economic rights as well as others that provide the subject to the exercise of citizenship. The theme of solidarity is attached to citizenship in that it means being supportive to each other offer the possibility of being a citizen, taking care, of giving and love, in the collective search for social justice and equality. From the analysis of citizenship and solidarity, a relation to theology was made, especially the theology of liberation and the public theology. Here we proposed to promote a needed debate to better understand the practice of these categories within the churches. To this end, we carried out a qualitative research concerning the social representation of the research subjects, on the various social work developed at the First Presbyterian Church of Vitoria, in line with the above categories. The collection and analysis of data allowed us to understand the level of understanding of church members about the social work and its connection with the practice of citizenship and solidarity.